The loyal one [large type] - Gray, Shelley Shepard (Gray, Shelley Shepard. Walnut Creek series, 2019)
When Katie Steury hires her old friend Harley Lambright to remodel her rundown old house into a charming bed and breakfast, she does so with trepidation. Though they are longtime friends, they've always had a rocky relationship, thanks to her being partly responsible for his most recent breakup. But while they may not always get along, she needs someone to trust with her secrets, and Harley is nothing if not trustworthy and loyal. Katie has always reminded Harley of a bright hummingbird-she is small and flighty, moves a mile a minute, and she possesses a very sharp beak. He's hesitant to accept the job because of his history with Katie. But when he realizes that Katie's been hiding her mother's hoarding, he agrees to help her because it's clear she needs someone on her side. Both soon discover that clearing the debris in one old house also means they have to do some clean-up in their lives, forcing them to reevaluate their past and their future. This somewhat painful process reveals that Katie isn't the only one with secrets. As the house gets a second chance, so, too, does their relationship. Now all they have to do is open their hearts-and hope and pray that their new bond will also stand the test of time.